Small-scale Intensity Mapping: Extended Halos as a Probe of the Ionizing Escape Fraction and Faint Galaxy Populations during Reionization - Mas-Ribas, Lluís; Hennawi, Joseph F.; Dijkstra, Mark; Davies, Frederick B.; Stern, Jonathan; Rix, Hans-Walter (The Astrophysical journal, 2017)
We present a new method to quantify the value of the escape fraction of ionizing photons, and the existence of ultra-faint galaxies clustered around brighter objects during the epoch of cosmic reionization, using the diffuse Ly , continuum, and H emission observed around galaxies at . We model the surface brightness profiles of the diffuse halos, considering the fluorescent emission powered by ionizing photons escaping from the central galaxies, and the nebular emission from satellite star-forming sources, by extending the formalisms developed in Mas-Ribas & Dijkstra and Mas-Ribas et al. The comparison between our predicted profiles and Ly observations at z = 5.7 and z = 6.6 favors a low ionizing escape fraction, , for galaxies in the range . However, uncertainties and possible systematics in the observations do not allow for firm conclusions. We predict H and rest-frame visible continuum observations with the James Webb Space Telescope (JWST), and show that it will be able to detect extended (a few tens of kiloparsecs) fluorescent H emission powered by ionizing photons escaping from a bright, , galaxy. Such observations could differentiate fluorescent emission from nebular emission by satellite sources. We discuss how observations and stacking several objects may provide unique constraints on the escape fraction for faint galaxies and/or the abundance of ultra-faint radiation sources.